2019
DOI: 10.5089/9781498314718.001
|View full text |Cite
|
Sign up to set email alerts
|

Informality and Gender Gaps Going Hand in Hand

Abstract: In sub-Saharan Africa women work relatively more in the informal sector than men. Many factors could explain this difference, including women's lower education levels, legal barriers, social norms and demographic characteristics. Cross-country comparisons indicate strong associations between gender gaps and higher female informality. This paper uses microdata from Senegal to assess the probability of a worker being informal, and our main findings are: (i) in urban areas, being a woman increases this probabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…In Sub-Saharan Africa, women are seen to dominate the informal sector when compared to men, mainly because of lower education level, legal barriers, social norms and demographic characteristics (Malta et al, 2019). Magidimisha & Gordon (2015) also reported that female informal enterprise owners in Southern Africa have different attributes from their male counterparts, while women in East Africa are disproportionately self-employed in informal enterprises, which increases their vulnerability and reduces their ability to access nances and services (Golla, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sub-Saharan Africa, women are seen to dominate the informal sector when compared to men, mainly because of lower education level, legal barriers, social norms and demographic characteristics (Malta et al, 2019). Magidimisha & Gordon (2015) also reported that female informal enterprise owners in Southern Africa have different attributes from their male counterparts, while women in East Africa are disproportionately self-employed in informal enterprises, which increases their vulnerability and reduces their ability to access nances and services (Golla, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ironically, unlike other regions, women dominate the informal economy in Africa with the harsh economic situation in the sector compared to the formal economy. Again, women experience another great discrimination and are pushed into the most vulnerable sector in Africa (UNU, 2013;Malta et al, 2019), with approximately 89.7 percent of employed women in Africa being in informal employment excluding agriculture and 92.3 percent when agriculture is included (ILO, 2018). Men and women in the informal sector face risks of unstable earnings and no access to health insurance.…”
Section: Introductionmentioning
confidence: 99%
“…The question of gender disparities in the labor market is still topical and, particularly so for the informal economy, which is expanding as economies face varieties of crises (Castellano & Rocca, 2019; ILO, 2018; Malta et al., 2019). This situation appears to be more critical in developing countries where institutional and market failures are engendering acute unemployment, underemployment, corruption, disparities, and poverty.…”
Section: Introductionmentioning
confidence: 99%
“…On informality and gender gaps in Sub-Saharan Africa, seeMalta, Kolovich, Martinez and Tavares (2019).©International Monetary Fund. Not for Redistribution…”
mentioning
confidence: 99%